Commento a «La bufera e altro» di Montale - Romolini, Marica (Premio Ricerca «Città di Firenze», 2012)
Despite the indisputable richness of the Montalian bibliography, there still was no comment on a fundamental collection such as La bufera e altro, published, after a complex and protracted gestation, by Neri Pozza in 1956. The aim of this book is to fill that void, giving a first contribution to the exegesis of one of Montale's densest - and most difficult - works, where the poet draws the conclusions of a long research to restart his own inexhaustible search for new languages and imagery. Between preliminary introductions (proper essays) and notes, she tries to take stock of the matter by comparing the various existing critical hypotheses and proposing - in a close hand-to-hand with the text, verse by verse, problematising rather than glossing over - an original interpretative line.